Biochar Amendment Alters the Nutrient-Use Strategy of Moso Bamboo Under N Additions - Gao, Jinpei; Li, Quan; Zhang, Junbo; Cui, Kunkai; Wu, Zhizhuang; Shi, Man; Song, Xinzhang (Frontiers in Plant Science, 2021)
Nutrient resorption can affect plant growth, litter decomposition, and nutrient cycling. While we know that N and biochar fertilizers affect soil nutrient concentrations and plant nutrient uptake, an understanding of how combined applications of N and biochar affect plant nutrient resorption in plantations is lacking. In this study, we applied N (0, 30, 60, and 90 kg N ha-1 yr-1 defined as N0, N30, N60, and N90, respectively) and biochar (0, 20, and 40 t biochar ha-1 defined as BC0, BC20, and BC40, respectively) to the soil of a Moso bamboo plantation. We investigated the effects of these treatments on N and P resorption by young and mature bamboo plants, as well as the relationship between nutrient resorption and leaf and soil nutrient concentrations. Young bamboo showed significantly greater foliar N resorption efficiency (NRE) and P resorption efficiency (PRE) than mature bamboo. N addition alone significantly increased the N resorption proficiency (NRP) and P resorption proficiency (PRP) but significantly decreased the NRE and PRE of both young and mature bamboo. In both the N-free and N-addition treatments, biochar amendments significantly reduced the foliar NRE and PRE of young bamboo but had the opposite effect on mature bamboo. Foliar NRE and PRE were significantly negatively correlated with fresh leaf N and P concentrations and soil total P concentration but significantly negatively correlated with soil pH. Our findings suggest that N addition inhibits plant nutrient resorption and alters the nutrient-use strategy of young and mature bamboo from “conservative consumption” to “resource spending.” Furthermore, biochar amendment enhanced the negative priming effect of N addition on nutrient resorption in young bamboo but reduced the negative effect on that of mature bamboo under N-addition treatments. This study provides new insights into the combined effects of N and biochar on the nutrient resorption of Moso bamboo and may assist in improving fertilization strategies in Moso bamboo plantations.